2020
DOI: 10.1029/2019jb017604
|View full text |Cite
|
Sign up to set email alerts
|

Basalts From the Chukchi Borderland: 40Ar/39Ar Ages and Geochemistry of Submarine Intraplate Lavas Dredged From the Western Arctic Ocean

Abstract: Submarine volcanism in the western Arctic Ocean, known as Amerasia Basin, is attributed to a mantle plume based on geophysics and meager geochemical evidence. Basaltic samples dredged from Chukchi Borderland within the basin have produced minimum 40Ar/39Ar ages for eruption at circa 118–112, circa 105–100, and circa 90–70 Ma, which we use to constrain tectonic models for basin opening. Major oxide and trace element concentrations and Sr, Nd, and Hf isotopic ratios of the lavas show that the circa 118–112 Ma sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 202 publications
(383 reference statements)
1
20
0
Order By: Relevance
“…1). These samples from the steep margins of the Chukchi Borderland, however, all are tholeiitic in composition (Mukasa et al, 2020). The timing and igneous make-up of the Alpha Ridge remains elusive, other than (i) dredged samples of alkaline basalt from the Alpha Ridge that yielded an Ar-Ar age of 90.40 ± 0.26 Ma (Wil-liamson et al, 2019a) and previously 89 ± 1 Ma (Jokat et al, 2013), (ii) ages of 127-110 Ma suggested for volcanic samples dredged at the Siberian end of the Mendeleev Ridge (Nikishin et al, 2020), and (iii) ages of ca.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1). These samples from the steep margins of the Chukchi Borderland, however, all are tholeiitic in composition (Mukasa et al, 2020). The timing and igneous make-up of the Alpha Ridge remains elusive, other than (i) dredged samples of alkaline basalt from the Alpha Ridge that yielded an Ar-Ar age of 90.40 ± 0.26 Ma (Wil-liamson et al, 2019a) and previously 89 ± 1 Ma (Jokat et al, 2013), (ii) ages of 127-110 Ma suggested for volcanic samples dredged at the Siberian end of the Mendeleev Ridge (Nikishin et al, 2020), and (iii) ages of ca.…”
Section: Introductionmentioning
confidence: 95%
“…118-112 Ma, ca. 105-100 Ma, and 90-70 Ma for dredge samples of the Chuckchi borderland (Mukasa et al, 2020). The compositions of the few dredged samples of the Alpha Ridge, with the exception of Van Wagoner et al (1986), have only been reported in abstracts without access to the whole rock data.…”
Section: Introductionmentioning
confidence: 99%
“…118-112 Ma, ca. 105-100 Ma, and 90-70 Ma for dredge samples of the Chuckchi borderland (Mukasa et al, 2020). The compositions of the few dredged samples of the Alpha Ridge, with the exception of Van Wagoner et al (1986), have only been reported in abstracts without access to the whole rock data.…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus from these samples is that Alpha Ridge was emergent or shallowly submerged. The in-situ samples consist predominantly of continental flood basalts derived from melting in the subcontinental lithospheric mantle and volcaniclastic sedimentary rock formed subaerially and shallow marine (e.g., Brumley 2009;Mukasa et al 2020) which also accounts for the limestone.…”
Section: Alpha Ridgementioning
confidence: 99%